Disponibilidade de formas de fósforo do solo às plantas - Gatiboni, Luciano Colpo (2003)
The soil phosphorus availability depends on a dynamic process and it involves its different forms in the soil. The bond energy of phosphorus and its ligants drives the desorption phenomenon and lability of the different forms. Therefore, the extractants used to estimate phosphorus availability may not represent all labile forms in soil. Four studies were carried out to evaluate the lability of soil phosphorus forms, the mechanism of action of some soil phosphorus extractants and the capacity of these in predict the availability to plants. Studies 1 and 2 were carried out to estimate the lability of soil phosphorus forms to plants and studies 3 and 4 to evaluate chemical extractors. The Study 1 consisted of fifteen successive croping in greenhouse and fractionation of soil phosphorus after each three cropings. Soil samples of a Rhodic Hapludox that had received 0, 180, 360, 540 and 720 kg ha-1 of P2O5 along six years of cultivation prior this study were used. In the Study 2, analyses of 31P-NMR were done in some soil samples collected from Study 1 to evaluate the behavior of the organic phosphorus forms after croping. In the Study 3, the mechanism of action of the extractants Mehlich 1, Mehlich 3 and Anion Exchange Resin (AER) was evaluated using successive extractions and then fractionation of soil phosphorus. In the Study 4 the evaluation of phosphorus availability was done by isotopic dilution with 32P, using some soil samples from the Study 1, and samples from different soils types under natural pasture or from experiments under different management systems. The results showed that the phosphorus supply to plants is sustained by available inorganic forms and when these decrease, other inorganic forms with smaller lability drives the supply, including recalcitrant forms. The organic forms were important only when inorganic forms remain very low. The extractors Mehlich 1, Mehlich 3 and AER had similar capacity to predict availability, although they had different mechanism of action. The isotopic dilution was not better than Mehlich 1, Mehlich 3 and AER to estimate phosphorus availability in soil.